2005
DOI: 10.1002/hep.20642
|View full text |Cite
|
Sign up to set email alerts
|

A key role for autoreactive B cells in the breakdown of T‐cell tolerance to pyruvate dehydrogenase complex in the mouse†

Abstract: The key immunological event in the pathogenesis of the autoimmune liver disease primary biliary cirrhosis is breakdown of T-cell self-tolerance to pyruvate dehydrogenase complex (PDC). The mechanism resulting in this breakdown of tolerance remains unclear. Mice exposed to self-PDC mount no immune response; however, animals coexposed to self-PDC and PDC of foreign origin (which in isolation induces a cross-reactive antibody but not an autoreactive T-cell response) show breakdown of T-cell as well as B-cell tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In those patients, as it has been shown in the present work, the presence of HLA-DR3 allele leads to a more diversified B-cell response. Finally, these strong correlations between specific HLA-DRB1 phenotypes and epitope spreading or antibody pattern suggest that autoantibodies to CYP2D6 may play a pathogenic role by enhancing the autoantigen presentation to T cells involved in the amplification of autoimmunity and progression of the disease as it has been described in other autoimmune diseases [37,38].…”
Section: Discussionmentioning
confidence: 91%
“…In those patients, as it has been shown in the present work, the presence of HLA-DR3 allele leads to a more diversified B-cell response. Finally, these strong correlations between specific HLA-DRB1 phenotypes and epitope spreading or antibody pattern suggest that autoantibodies to CYP2D6 may play a pathogenic role by enhancing the autoantigen presentation to T cells involved in the amplification of autoimmunity and progression of the disease as it has been described in other autoimmune diseases [37,38].…”
Section: Discussionmentioning
confidence: 91%
“…An unsolved mystery in the pathogenesis of PBC is the mechanism for breakdown of T-cell tolerance to self-PDC. Robe and colleagues [10 ] used an in-vivo active and passive transfer approach to test the theory that the breakdown of T-cell tolerance to PDC can be driven by the presence of B-cells and/or antibodies cross-reactive with self-PDC. They found that naïve female SJL/J mice had breakdown of T-cell tolerance to self-PDC when exposed to self-PDC mixed with B-cells expressing surface Ig reactive with self-PDC, but breakdown of T-cell tolerance did not occur if the mice were exposed to self-PDC or self-PDC-reactive B-cells in isolation.…”
Section: Pathogenesismentioning
confidence: 99%
“…Patients with PBC have high titres of anti-PDC antibodies. 90,91 The peripheral component of fatigue in patients with PBC was thought to be linked to their inability to sustain repeated muscle contractions. Using a novel magnetic resonance spectroscopy technique, it has been shown that fatigued patients have marked muscle acidosis related to mitochondrial dysfunction and prolonged recovery time, which in turn was related to serum anti-PDC levels.…”
Section: Management Of Fatigue In Pbcmentioning
confidence: 99%